2020
DOI: 10.1021/acsinfecdis.0c00166
|View full text |Cite
|
Sign up to set email alerts
|

HSF1 Activation Can Restrict HIV Replication

Abstract: Host protein folding stress responses can play important roles in RNA virus replication and evolution. Prior work suggested a complicated interplay between the cytosolic proteostasis stress response, controlled by the transcriptional master regulator heat shock factor 1 (HSF1), and human immunodeficiency virus-1 (HIV-1). We sought to uncouple HSF1 transcription factor activity from cytotoxic proteostasis stress and thereby better elucidate the proposed role(s) of HSF1 in the HIV-1 lifecycle. To achieve this ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…We anticipate this knowledge will prove particularly valuable for ongoing efforts to target host proteostasis network components for antiviral therapeutics [52,[74][75][76][77][78] and for the design of proteostasis network-targeted therapeutic adjuvants that can prevent the emergence of viral variants that confer immune system escape or drug resistance. More broadly, the principles observed here seem likely to prove generally applicable, not just to viral proteins but also endogenous client proteins…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipate this knowledge will prove particularly valuable for ongoing efforts to target host proteostasis network components for antiviral therapeutics [52,[74][75][76][77][78] and for the design of proteostasis network-targeted therapeutic adjuvants that can prevent the emergence of viral variants that confer immune system escape or drug resistance. More broadly, the principles observed here seem likely to prove generally applicable, not just to viral proteins but also endogenous client proteins…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we assessed whether these perturbations of the ER proteostasis environment had deleterious effects on cell viability or restricted HIV replication, as we had previously observed inhibition of HIV replication upon upregulation of the heat shock response [52]. To address the former, we activated XBP1s and/or ATF6 in SupT1 DAX cells and measured resazurin metabolism 72 h post-drug treatment (S1 Fig A ).…”
Section: Chemical Genetic Control Of Er Proteostasis Network Composition During Hiv Infectionmentioning
confidence: 99%
“…We assessed whether these perturbations of the ER proteostasis environment had deleterious effects on cell viability or restricted HIV replication, as we had previously observed inhibition of HIV replication upon upregulation of the heat shock response [52]. To address the former, we induced XBP1s and ATF6, individually or simultaneously, in SupT1 DAX cells and measured resazurin metabolism 72 h after drug treatment (S2A Fig) . We observed that induction of XBP1s and ATF6, either separately or simultaneously, did not alter the metabolic activity of SupT1 DAX cells, consistent with no deleterious effects on cell viability.…”
Section: Chemical Genetic Control Of Er Proteostasis Network Composit...mentioning
confidence: 99%
“…We also find that evolutionary interactions between viral proteins and host proteostasis factors are specific to the virus type, as well as to specific regions of the viral protein. We anticipate that this knowledge will prove particularly valuable for ongoing efforts to target host proteostasis network components for antiviral therapeutics [52,[81][82][83][84][85][86] and for the design of proteostasis-network-targeted therapeutic adjuvants that can prevent the emergence of viral variants that confer immune system escape or drug resistance. More broadly, the principles observed here seem likely to prove generally applicable not just to viral proteins but also to endogenous client proteins.…”
Section: Plos Biologymentioning
confidence: 99%
“…4M). Of note, previous studies have shown that HSF1, as a stress-induced and DNA-binding transcription factor, could participate in regulating HIV-1 transcriptional activation and latent escape [53,54], and the IRF family members as interferon regulatory factors could play vital regulatory roles in the upstream of antiviral immunity and in ammation [55,56]. Additionally, our results demonstrated that many disordered genes in ciliated cells for cleaning up mucus, were mainly enriched in these biological processes such as protein translation, transcription initiation, microtubule movement, cilia assembly and cilia structure (Fig.…”
Section: Lung In Ammation Drives the Increase Of Brosis And Mucus Acc...mentioning
confidence: 99%